Pyrimidine-Piperazine Hybrids as Potential PARP1 Inhibitors: Dual in silico and in vitro Approaches against Breast Cancer - Shivakumar, Rashmi; Beeraka, Narasimha M.; Swaroop, Toreshettahally R.; Xi, Zhang; Vinay Kumar, D.C.; Hidayathulla, Syed; Basappa, Basappa (Asian Journal of Chemistry, 2026)
Pyrimidine derivatives are known to possess notable anticancer properties. In this study, a new series of pyrimidine-piperazine hybrid compounds (8a-j) was synthesised and evaluated for cytotoxic and PARP1 inhibitory activities against MCF-7 breast cancer cells. The IC50 values against this cell line were determined by Alamar blue assay. The poly(ADP-ribose) polymerase-1 (PARP1) catalytic activity was assessed through a fluorescence-based enzymatic assay. Among the synthesised compounds, 8e demonstrated the highest potency with an IC50 of 10.45 µM, showing significant PARP1 inhibition. Docking analysis revealed strong and specific binding of 8e to the PARP1 active site, supporting the experimental data.